Peripapillary arterial ring of Zinn-Haller in highly myopic eyes as detected by optical coherence tomography angiography - Ishida, Tomoka; Jonas, Jost B. (Retina, 2017)
Purpose: To visualize the arterial circle of Zinn-Haller (ZHAC) in highly myopic patients by using OCT-A. Methods: Two hundred and fifty-three eyes of 146 consecutive patients with axial length ≥26.5 mm who underwent OCT-A centered onto the optic disk were studied. Results: Arterial circle of Zinn-Haller was detectable on OCT-A images within the area of the parapapillary myopic conus in 26 (10%) of 253 eyes. The ZHAC was annular in 18 (69%) eyes, triangular in (15%) 4 eyes, and irregular (15%) in 4 eyes. The visibility of the ZHAC on OCT-A images was similar to the visibility on indocyanine green angiograms and significantly better than on conventional fundus photos. Optical coherence tomography angiography visualized details of the ZHAC including the entry of the short posterior ciliary arteries into the circle up to the branches in direction to the optic nerve and ZHAC-associated cilioretinal arteries. In three eyes, the ZHAC was composed of multiple rings. Conclusion: Noninvasive OCT-A allowed the visualization of ZHAC up to smaller vessel branches in 10% of highly myopic eyes. Because ZHAC is the main blood supply to lamina cribrosa of optic nerve, OCT-A-based assessment of ZHAC could become of interest in diseases such as glaucomatous optic neuropathy.
Gesehen am 13.09.2018